Patent overview: Device for fingerprint identity guarantee - Lalović, Komlen G. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The patent device named “Device for biometric identification of maternity” is a dual fingerprint scanner that provides data of mother and baby fingerprints at the very moment of birth and further guarantees the maternity of a newborn baby by generating a unique ID reference and encrypting that data with the highest level of protection. For the first time, we enrolled qualitative research that proves a baby’s identity at the very moment of birth based on the fingerprint minutiae. No one has done it until today! The realised technical solution scans, processes, stores, saves and encrypts personal data with one main purpose - to prove maternity of every newborn baby with 100% accuracy. By fingerprint scanning of both the mother and the baby’s fingerprints simultaneously at the very moment of birth, ID is generated and stored. This allays potential fear of babies being replaced. Every identity is guaranteed. By encrypting this data, the whole process is raised to the highest security and confidentiality levels in maternity wards worldwide. In each case, the fear that almost every mother has in this period is allayed as well as the question: “Is this my baby?”